Full Width-Half Maximum Characteristics of FBG for Petroleum Sensor Applications - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2020)
In this paper, we have analyzed the full width-half maximum (FWHM) response of a uniform fiber Bragg grating (FBG) for petroleum sensor applications numerically. The analysis; which is depending on parameters such as the gratings length (Lg) and the amplitude of an induced index profile (Δn) change have successfully investigated using MATHCAD software. From the numerical simulation, there is an effect of the Lg and the Δn on the FWHM response. Results show the Lg value that effect the FWHM response is ≤7 mm. In contrast, results show that there is no effect of temperature on the FWHM response. In light of the increasing demand for a wide FWHM band within the applications of optical sensor technology, the results obtained are very important, especially in the field of petroleum industry.